Applying the WEF nexus at a local level: a focus on catchment level - Walker, S.; Jacobs-Mata, Inga; Fakudze, Bhekiwe; Phahlane, M. O.; Masekwana, N. (Elsevier, 2022)
The currently used water–energy–food (WEF) nexus philosophy and frameworks integrate the interconnections across the water, energy, food-agricultural sectors using a systems perspective. There are many challenges to model the interdependencies and trade-offs using a WEF nexus approach. Many tools and indices have been developed and used at the regional and national levels. However, there are few attempts to apply tools at a local and/or catchment level as described in this chapter for the Inkomati-Usuthu catchment in South Africa. The available tools were described according to inputs required and outputs produced together with both spatial and temporal scales and potential users. The data requirements for each sector were unpacked, and potential sources for local information are listed despite the wide set of data necessary. The way forward to applying these tools in the Crocodile and lower Komati river basins was considered in light of the facilitated stakeholder engagement to promote understanding of the scope of the WEF nexus and economic and policy implications.